Comparison of aspartate aminotransferase platelet ratio index score and insulin resistance in type 2 diabetes mellitus with non-alcoholic fatty liver disease - Gupta Nikhil; Ramzaan Dar Waseem; Wani Asma; Raj Saxena Rachit; Khatri Sahil; Tyagi Bhumesh; Bansal Pankaj; Ahmad Mir Irfan (Endocrine Regulations, 2023)
Objective. Nonalcoholic fatty liver disease (NAFLD) is a spectrum of liver diseases characterized by the presence of ectopic fat in the liver and steatosis, which cannot be explained by alcohol consumption. The association between NAFLD and type 2 diabetes mellitus (T2DM) is well established. As liver fibrosis progresses in a patient with NAFLD, insulin resistance (IR) increases and may worsen diabetes control. The aspartate aminotransferase platelet ratio index (APRI) score is a simple and inexpensive bedside marker that can detect liver fibrosis and cirrhosis. Several studies have shown an association between APRI and NAFLD. However, there is a gap in correlation with IR in patients with diabetes. In this study, we sought to correlate IR and NAFLD in diabetes using the APRI score.